Nanostructured and photoelectrochemical systems for solar photon conversion - Archer, Mary D.; Nozik, Arthur J., 1936- (Imperial College Press ; World Scientific Pub. Co., 2008)
In this book, expert authors describe advanced solar photon conversion approaches that promise highly efficient photovoltaic and photoelectrochemical cells with sophisticated architectures on the one hand, and plastic photovoltaic coatings that are inexpensive enough to be disposable on the other. Their leitmotifs include light-induced exciton generation, junction architectures that lead to efficient exciton dissociation, and charge collection by percolation through mesoscale phases. Photocatalysis is closely related to photoelectrochemistry, and the fundamentals of both disciplines are covered in this volume.
Keywords: Photoelectrochemistry.; Nanostructured materials.; Solar energy.; Photocatalysis.; elektronické knihy; electronic books